The Sun and Moon are Larger by About 1.4% than we Think - Abunaieb, Salah (Transactions on Engineering and Computing Sciences, 2025)
This is a simple geometric modification to the currently recorded sizes of the sun and moon. The concept is based on the well-known observation that when looking at an object, it appears to progressively taper off toward its distant end. Spherical objects are no exception, even though their apparent tapering is not readily noticeable due to their unique geometry. As shown in this study, when looking at the solar disc or at the moon, we are actually looking at the base side of a seemingly slightly egg-shaped sun or moon. Given that the sun and moon are spherical in reality, the geometrically adjusted sizes show that each is about 1.4% bigger in volume than currently thought.